PROSA, MEMÓRIAS, TROTES E POESIA: UMA LEITURA DE WILSON BUENO E DE JOSELY VIANNA BAPTISTA - FELLINI, ALEXANDRE (2020)
This work aims to analyze works by contemporary Brazilian authors, Wilson Bueno and Josely Vianna Baptista. The research is divided into three chapters. Initially, is analyzed the narrative Meu Tio Roseno, a Cavalo (2000), by Wilson Bueno, from the perspective of narrative studies and narrator, evidencing the characteristics of the modern narrator and specific aspects of the history of 20th century history. As theoretical support, it is used, mostly, Walter Benjamin (1987), discussing the narrator’s conception and, from this, leading the analysis to the concepts of orality, experience. In the second chapter the book is analyzed in order to understand the character's journey while a symbology that involves travel, time and text space. There is a subchapter, still in the second chapter, in which it is about the war memories referring to the character Roseno. For this purpose, we consult other theorists, as Ricardo Piglia (2004), Umberto Eco (1991) e Andreas Huyssen (2001), discussing the notion of an artwork and its transformations, as well as discussions about Post-War memory, accumulation of information and oblivion, respectively. In the third chapter there is a comparative analysis between poems of Wilson Bueno and Josely Vianna Baptista, involving the themes of contemplation and poetic images creation. For this, we resort to the texts by Rosalind Krauss (1984), Décio Pignatari (1989) and Alfredo Bosi (1994) to understand the composition/structure of poetic texts, and texts by Maria Esther Maciel (2007) to explore the metaphor between human and animal behavior.